Increased epicardial fat tissue is a marker of subclinical atherosclerosis in patients with psoriasis. (31st October 2013) - Bulbul Sen, B.; Atci, N.; Rifaioglu, E.N.; Ekiz, O.; Kartal, I.; Buyukkaya, E.; Kurt, M.; Karakas, M.F.; Buyukkaya, S.; Akcay, A.B.; Sen, N.
Summary: Background: Carotid intima–media thickness (CIMT) is a potential indicator of subclinical atherosclerosis in patients with psoriasis. Epicardial fat thickness (EFT) is proposed as a new cardiometabolic risk factor. Objective: To evaluate the association between EFT and CIMT in patients with psoriasis. Methods: This was a cross‐sectional and observational study; 65 patients with psoriasis and 50 age‐ and sex‐ matched control subjects were included. Data about echocardiographic EFT, CIMT, anthropometric measurements and metabolic profile were obtained. Results: The EFT and CIMT were significantly increased (7·3 ± 0·5 vs. 6·5 ± 0·5 mm, P < 0·01; 0·74 ± 0·11 vs. 0·60 ± 0·07 mm, P < 0·01, respectively) in patients with psoriasis compared with the controls. EFT was significantly correlated with CIMT ( r = 0·69, P < 0·01). In a multiple linear regression model in which EFT was independently associated with psoriasis (β = 0·45, P < 0·01), age (β = 0·33, P = 0·01), CIMT (β = 0·50, P < 0·01), body mass index (β = 0·25, P = 0·01), high‐sensitivity C‐reactive protein (β = 0·32, P < 0·01) and duration of disease (β = 0·34, P = 0·03). Conclusions: We demonstrated that EFT and CIMT are increased in patients with psoriasis, and that echocardiographic EFT is closely correlated with CIMT in patients with psoriasis. The echocardiographic assessment of EFT may have the potential to be a simple marker of subclinical atherosclerosis and increased cardiovascular risk in patients with psoriasis. Abstract : What's already known about this topic? The risk of myocardial infarction, stroke and cardiovascular mortality increases in patients with psoriasis. Carotid intima–media thickness (CIMT) is a potential indicator of subclinical atherosclerosis in patients with psoriasis. Epicardial fat thickness (EFT) is proposed as a new cardiometabolic risk factor. What does this study add? EFT and CIMT are increased in patients with psoriasis compared with healthy controls. Echocardiographic EFT is closely correlated with CIMT in patients with psoriasis. The echocardiographic assessment of EFT may have the potential to be a simple marker of subclinical atherosclerosis and increased cardiovascular risk in patients with psoriasis.